The Analysis Of Misleading Information On Covid-19 Posted On Facebook - Sofia Hayati Yusoff; Fauziah Hassan; Fatin Nur Aqilah Isa (USIM Press, 2024)
Vol. 33 No. S5 (2021): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences